PENENTUAN PRIORITAS ALTERNATIF KEBIJAKAN SISTEM PRODUKSI BERDASARKAN PENDEKATAN NON NUMERIC MULTIEXPERTS MULTICRITERIA DECISION MAKING: STUDI KASUS PT X - Nurhasanah, Nunung (Industrial and Systems Engineering Assessment Journal (INASEA), 2006)
There are so many policy alternatives that should be faced by decision maker in industrial manufacturing. In order to determine the policy alternatives, Non Numeric Multi Experts Multi Criteria Decision Making has been chosen to solve the problem. The research purposes is to determine policy alternative priority of production system based on experts point of view using Non Numeric ME-MCDM approach.Â